Pengaruh Green Finance terhadap Pertumbuhan Ekonomi - Aleka Perti Jenia; Fenny Marietza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to measure the effect of green finance on economic growth. To create a sustainable economy, green finance supports investment in projects that have a positive impact on the environment. Green finance is measured by Green Banking while economic growth is measured by the rate of economic growth. Secondary data from provinces in Indonesia before the expansion were used in this study, namely 34 provinces. This study uses a quantitative approach. In addition, by using total sampling, where each member of the population is taken as a sample. Legitimacy theory is used in this study to emphasize the importance of social legitimacy for sustainable business practices and stakeholder theory to assess the impact of Green Finance on economic growth by considering the interests of various stakeholders. In this study, green finance is used as an independent variable and economic growth is used as a dependent variable. The results of the study indicate that Green finance has a negative effect on economic growth, meaning that the implementation of green finance, especially through the concept of Green Banking, can have a negative effect on economic growth. Green Finance projects usually require large initial costs so that they can inhibit economic growth.